2003
DOI: 10.1007/s00294-003-0393-4
|View full text |Cite
|
Sign up to set email alerts
|

Ditercalinium chloride, a pro-anticancer drug, intimately associates with mammalian mitochondrial DNA and inhibits its replication

Abstract: Ditercalinium chloride was originally synthesized for use as an anticancer drug and was then found to deplete mitochondrial DNA. Ethidium bromide is widely used to deplete mitochondrial DNA and produce mitochondrial DNA-less cell lines. Although ethidium bromide is used in the case of human cell lines, it frequently fails to deplete mitochondrial DNA in mouse cells. In contrast, ditercalinium chloride can deplete mitochondrial DNA in both mouse and human cells. However, little is known of the mechanisms by whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 26 publications
1
20
0
2
Order By: Relevance
“…19 Moreover, it has been demonstrated that in living cells EB stains mtDNA in nucleoids with fluorescence intensity that varies from one nucleoid to the other. 15,17 A similar result was also obtained for DC, 18 which is also an intercalating nucleic acid fluorescent probe. It has been also reported that EB blocks mtDNA replication, 20,21 inhibits DNA polymerase γ, 22 and that a long-term exposition to EB is used to deplete human cells of their mtDNA.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…19 Moreover, it has been demonstrated that in living cells EB stains mtDNA in nucleoids with fluorescence intensity that varies from one nucleoid to the other. 15,17 A similar result was also obtained for DC, 18 which is also an intercalating nucleic acid fluorescent probe. It has been also reported that EB blocks mtDNA replication, 20,21 inhibits DNA polymerase γ, 22 and that a long-term exposition to EB is used to deplete human cells of their mtDNA.…”
supporting
confidence: 65%
“…In living cells, nucleoids have been studied by noninvasive fluorescence microscopy, targeting fluorescent proteins to nucleoids, 10,14 or using supravital nucleic acid fluorescent probes, like ethidium bromide (EB) 10,[15][16][17] and ditercalinium chloride (DC). 18 We should recall that EB is an intercalating nucleic acid probe widely used to quantify the DNA content in fixed cells. On the contrary, it has been shown that in living cells nuclear DNA accessibility to EB is restricted only to a few DNA regions in active replication and/or transcription.…”
mentioning
confidence: 99%
“…However, it has been reported in the literature that these molecules can penetrate damaged plasmic and nuclear membranes of animal cells [20,21]. They are genotoxic and mutagenic because of their strong binding affinity to nuclear DNAs and RNAs via intercalation, and thereby blocking the gene replication and transcription processes [22][23][24][25][26][27]. Ideally, if one could find ways to carry these strong oligonucleotide intercalators through the intact plasmic membrane of a healthy live cell, while preventing them from entering the nucleus, it would be possible to design a phenanthridinium-based system for the selective sequestration of cytoplasmic oligonucleotides, i.e., messenger RNAs.…”
Section: Introductionmentioning
confidence: 98%
“…40 In addition, it is assumed to associate with mitochondrial DNA, inhibiting its replication. 41 Elinafide (LU 79553) is a bis intercalator derived from the naphthalimide pharmacophore 42 that exhibited excellent antitumor activity and reached phase I clinical trials, 43 showing anti-neoplastic activity in ovarian cancer, breast cancer, and mesothelioma. Many mechanistic studies on elinafide and its analogs have been undertaken, 44 but this drug has neuromuscular dose-limiting toxicity that has halted its clinical development.…”
Section: Bifunctional Intercalating Agentsmentioning
confidence: 99%